Thermodynamic study of zirconium carbide synthesis via a low-temperature pyrovacuum method - Arianpour, Farzin; Kazemi, Faramarz; Rezaie, Hamid Reza (Springer Science and Business Media LLC, 2019)
In this research, the thermodynamic aspect of the nano-sized zirconium carbide production is investigated via a facile, low-temperature and cost-effective carbothermal method under vacuum and argon atmospheres. The starting materials were zirconium acetate and sucrose as zirconium and carbon precursors, respectively. The gels were prepared based on 3, 4, 5, and 7 molar ratios of carbon to zirconium and heated at 1200 and 1400 °C under vacuum and argon atmospheres. The formation of zirconium carbides under different atmospheres were studied via thermogravimetric analysis and the results were compared. The phase composition and microstructural features were investigated using X-ray diffraction and scanning electron microscopy, respectively. According to the thermogravimetric results and performed thermodynamic calculations, it was revealed that the ZrC formation starts at 1200 °C under vacuum. It is also demonstrated that the formation of nano ZrC powder with crystallite sizes smaller than 30 nm, completely occurs after processing at 1400 °C in vacuum. The measured lattice parameter value of the optimized sample was equal to 4.7003 A.
Keywords: 7. Clean energy